PENGARUH PANJANG SIANG DAN MALAM TERHADAP WAKTU SALAT DI WILAYAH MAKASSAR - Mubarak, Mas’um; Akib, Faisal (HISABUNA: Jurnal Ilmu Falak, 2025)
Abtsract: This article contains the main problem being studied, namely how the length of the day and night affects prayer times in the Makassar region with 2 sub-problems, namely: What are the factors that cause variations in the length of the day and night in the Makassar region and What is the impact of the length of the day and night on prayer times in the Makassar region. This research uses library research. There are two approaches to this research, namely the syar'i approach because it examines Islamic law related to the arguments of the Koran and hadith and the astronomical approach because it discusses matters related to astronomy. Primary data sources in this research are books and secondary data sources were obtained from previous research. Data processing and data analysis techniques include: data identification, reduction, editing and conclusion. The results of this research show that variations in the length of day and night have a significant impact on prayer times in the Makassar area, through analysis of differences in the length of day and night on each day throughout the year, by taking a sample of prayer schedules throughout the time on the Muslim Pro application. The prayer times for each day throughout the year are not always the same, resulting in people being misled into carrying out the five daily prayers at different times than the actual times. The variation factors in the length of day and night or what underlies the length of day and night are the rotation and revolution of the earth. The implication of this research is that it is hoped that the government or religious leaders can expand the understanding of Muslims who still or do not understand at the beginning of each prayer time which changes every day and is not fixed at certain times, as well as ensuring that prayers are carried out on time. It is also hoped that students, especially sharia and law faculties and astronomy departments, can play an active role in providing knowledge to the public regarding prayer time schedules, in order to avoid praying prayers out of time.